2012
DOI: 10.1155/2012/715024
|View full text |Cite
|
Sign up to set email alerts
|

Kappa-Opioid Receptors in the Caudal Nucleus Tractus Solitarius Mediate 100 Hz Electroacupuncture-Induced Sleep Activities in Rats

Abstract: Previous results demonstrated that 10 Hz electroacupuncture (EA) of Anmian acupoints in rats during the dark period enhances slow wave sleep (SWS), which involves the induction of cholinergic activity in the caudal nucleus tractus solitarius (NTS) and subsequent activation of opioidergic neurons and μ-receptors. Studies have shown that different kinds of endogenous opiate peptides and receptors may mediate the consequences of EA with different frequencies. Herein, we further elucidated that high-frequency (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 33 publications
5
24
0
1
Order By: Relevance
“…Nevertheless, REM sleep during the following light period was decreased from 15.3 ± 1.3% obtained from the undisturbed baseline to 11.5 ± 1.1% acquired from rats treated with 100 Hz EA stimuli (p < 0.05, Figure 2F). There was no change, except that the sleep suppression caused by ketamine during the first 4-h postadministration, in the sleep-wake activity when rats received the sham EA stimulation (the sham group, Figure 1A & 1B), which is consistent with our previous results [11,30]. This observation indicated that high-frequency EA stimulation of bilateral Feng-Chi acupoints did not alter NREM sleep, but decreased REM sleep during the light period in normal rats.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, REM sleep during the following light period was decreased from 15.3 ± 1.3% obtained from the undisturbed baseline to 11.5 ± 1.1% acquired from rats treated with 100 Hz EA stimuli (p < 0.05, Figure 2F). There was no change, except that the sleep suppression caused by ketamine during the first 4-h postadministration, in the sleep-wake activity when rats received the sham EA stimulation (the sham group, Figure 1A & 1B), which is consistent with our previous results [11,30]. This observation indicated that high-frequency EA stimulation of bilateral Feng-Chi acupoints did not alter NREM sleep, but decreased REM sleep during the light period in normal rats.…”
Section: Resultssupporting
confidence: 91%
“…Our results indicated that 100 Hz stimulation of bilateral Feng-Chi acupoints elicited no significant effect in the physiological sleep in normal rats, whereas EA stimuli further deteriorated pilocarpineinduced decreases of NREM sleep and REM sleep. Referring to our previous finding that 100 Hz EA stimulation of Anmian acupoints, which locate near by the FengChi acupoints, enhances physiological sleep in normal rats [11], suggesting the effect of high-frequency EA of Feng-Chi acupints involves a specific mechanism. These observations, since they subvert the functions of FengChi acupoints documented in the Lingshu Jing, surprise us.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…A teflon coated stainless steel bipolar metal wire electrode (0.005" bare, 0.008" coated, A-M systems, Inc. WA) was implanted into the brain NTS with stereotaxic coordination according to rat brain stereotaxic atlas of Paxinos' and Watsons' [28]: AP:-14.04 mm to bregma; ML:0.4 mm, and DV:8 mm from the dura respectively. All implants were fixed to the skull by dental acrylic cement and two stainless steel glass anchor small screws [29,30]. Establishment of microelectrodes at the right site was confirmed by passing the DC through the active wire in order to making lesion at electrode tip point and histological section performed at the end of experiments.…”
Section: Surgerymentioning
confidence: 99%